IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMBELAJARAN BAHASA INDONESIA KELAS X DI SMK NEGERI 2 SAROLANGUN - Damayanti, Elfa; Emidar; Ermawati Arief; Delsy Arma Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Merdeka Curriculum in Indonesian language learning for class X at SMK Negeri 2 Sarolangun, focusing on planning, implementation, as well as identifying obstacles and supporting factors. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews with the school principal and Indonesian language teacher, and documentation analysis. Data were analyzed using Miles and Huberman's interactive model consisting of data reduction, data display, and conclusion drawing. Findings reveal that curriculum planning remains at the initial stage, characterized by high dependency on standardized modules from the Ministry without significant local contextualization. However, implementation shows developing dynamics, particularly in assessment integration and teacher reflection. Major obstacles include infrastructure limitations specifically three-year electrical failures in several classrooms and limited teacher capacity due to insufficient training. The primary supporting factor is teacher resilience, exemplified by proactive adaptation such as utilizing the Computer Laboratory as an alternative facility during power outages. The study concludes that implementation at SMK Negeri 2 Sarolangun represents creative adaptation where human agency (teacher dedication) compensates for physical and administrative infrastructure limitations.